Transient Behavior of CFRP Tensegrity System in a Suspen dome - IfeOlorun Olofin; Ronggui Liu (Civil Engineering Journal, 2017)
In order to establish a conclusive result for the application of carbon fibre reinforced polymer (CFRP) cable as a tensegrity system for a suspen dome, the structural integrity assessment of the system, subjected to transient load, must be considered. This paper gives a preliminary assessment of the dynamic behavior of carbon fibre reinforced polymer cable in a suspen dome in comparison with that of the steel counterpart, using a small model of 4 m span and 0.4 m rise. A commercial finite element software namely ANSYS was used for the structure simulation in respect of the experimental design. The results from the simulation show that the carbon fibre reinforced polymer cable gives a reliable assessment as the steel counterpart. The natural frequencies of CFRP cables are higher than those of steel cables due to the CFRP cables’ high stiffness-to-weight ratio and less curvature under gravity loads. CFRP cables influence the structure with good stiffness which provides good vibration resistance. The results also indicate that from a technical point of view, carbon fibre reinforced polymer cables can perform better than steel cables as tensegrity system for a suspen dome. It is concluded that CFRP cables can be applied to replace steel ones as tensegrity system for a suspen dome.